Transnational Ideologies: A Threat to Values of Pancasila and National Character of Indonesian Citizens Abroad - Mulyadi, Dian Muhammad Johan Johor; Nurdin, Encep Syarief; Ruyadi, Yadi; Najib, Agus Mohammad; Dewantara, Jagad Aditya (Jurnal Moral Kemasyarakatan, 2025)
Indonesian citizens abroad are vulnerable to being influenced by foreign ideologies that are contrary to Pancasila, both those that lead to radicalism-terrorism, those exposed to communism-atheism, and those that show liberalism-westernism. The purpose of this study is to compare various groups of Indonesian citizens abroad, especially Indonesian migrant workers in Tawau, Malaysia, and to analyze how exposure to the above-mentioned transnational ideologies impacts their understanding of Pancasila values and threatens their national character after returning to Indonesia. In this study, an autoethnographic methodology was used. The results of this study are to force the Indonesian Government to create a strategy to protect Indonesian citizens abroad. This strategy will be called the Internationalization of Pancasila Ideology Development. The conclusion of this study is that without implementing the Pancasila Internationalization strategy for Indonesian citizens abroad, the transnational ideological values that are contrary to the Pancasila they adhere to upon returning from abroad will be forcibly disseminated as has happened recently, causing unrest and security disturbances in Indonesia.